Genesis of the Bagenheigeqier Pb–Zn skarn deposit in Inner Mongolia, NE China: constraints from fluid inclusions, isotope systematics and geochronology. (16th February 2021) - Cai, Wen-yan; Wang, Ke-yong; Li, Jian; Fu, Li-juan; Li, Shun-da; Yang, He; Konare, Yassa
Abstract: Most skarns are found near the pluton or in lithologies containing at least some limestone. However, recent research has shown that neither a pluton nor limestone is necessarily required to form a skarn deposit. The newly discovered Bagenheigeqier Pb–Zn skarn deposit is located in NE China. The skarn and Pb–Zn orebodies occur in volcanic lithologies of the Baiyin'gaolao Formation and are controlled by NE–SW-trending faults. The nearest pluton is a granite porphyry, at a distance of 20–250 m from the orebodies. Five paragenetic stages at Bagenheigeqier are recognized: (I) skarn; (II) oxide; (III) early sulphide; (IV) late sulphide; and (V) late quartz–calcite. The fluid inclusions from stages II to V homogenized at temperatures of 402–452, 360–408, 274–319 and 167–212°C, respectively. The hydrogen and oxygen isotope compositions (δ 18 OH2O, –12.4‰ to +9.3‰; δDH2O, –156.5‰ to –99.1‰) indicate that the ore-fluids were primarily of magmatic origin, with the proportion of meteoric water increasing during the progression of ore formation. Sulphur isotope values (δ 34 SVCDT, 1.4–5.5‰), lead isotope values ( 206 Pb/ 204 Pb, 18.184–18.717; 207 Pb/ 204 Pb, 15.520–15.875; 208 Pb/ 204 Pb, 37.991–38.379) and the initial 187 Os/ 188 Os ratios of the pyrite (0.307 ± 0.06) suggest that the ore metals were derived from the granite porphyry and Baiyin'gaolao Formation. Re–Os dating of pyrite intergrown with galena and sphalerite yielded a well-constrained isochron age of 151.2 ± 4.7 Ma, which is coeval with the laser ablation – inductively coupled plasma – mass spectrometry zircon U–Pb age of 154 ± 1 Ma for the granite porphyry. The deposit was therefore formed during Late Jurassic time.